Corporate social responsibility at the intersection of state and market: CSR interpretation in China - Xu Kang (Business and Society Review, 2025)
This article explores the interpretation of corporate social responsibility (CSR) in an authoritarian context, with a specific focus on China. Despite surged CSR disclosures by Chinese firms, their understanding and application of CSR often align more with the party-state's policy directives than with international self-regulation standards. By analyzing CSR narratives from various actors, including government agencies, corporations, and third parties, through the lens of institutional logics, this article provides a comprehensive exploration of the influence of authoritarian capitalist institutions on CSR interpretation in China, offering theoretical insights into business and human rights issues within authoritarian state contexts.
Keywords: 330; authoritarian capitalism; authoritarian state; China; corporate social responsibility; institutional logic; institutional theory